Dynamical algebra of quasi-exactly-solvable potentials - Dutra, Alvaro de Souza [UNESP]; Filho, Henrique Boschi (American Physical Soc, 1991)
We show that by using second-order differential operators as a realization of the so(2,1) Lie algebra, we can extend the class of quasi-exactly-solvable potentials with dynamical symmetries. As an example, we dynamically generate a potential of tenth power, which has been treated in the literature using other approaches, and discuss its relation with other potentials of lowest orders. The question of solvability is also studied. © 1991 The American Physical Society.